PRELIMINARY STUDY OF MATERIAL PROPERTIES ON PU-MG-ZN FOR ANEURYSM CLIP APPLICATION - Made Subekti Dwijaya; Talitha Asmaria (National Research and Innovation Agency (BRIN), 2022)
An aneurysm clip is an implant tool for assisting the neurosurgeon in treating acute hemorrhagic stroke and cerebral aneurysm. This equipment stops the blood flow of a ruptured or enlarged blood vessel or aneurysm. In the development of aneurysm clip production, titanium alloy is the most used material selection. Several researchers reported that this metal leads to artifacts during MR (magnetic resonance) or CT (computed tomography) imaging. Since several pieces of evidence polyurethane could be a good material selection for aneurysm clips, this paper aims to investigate the material properties of the polyurethane foam with an additional combination of magnesium and zinc. This study conducts magnesium and zinc composition variations of 1 wt.%, 2 wt.%, and 3 wt.%, respectively. The materials were tested using a compression test, a FTIR (fourier-transform-infrared), SEM (scanning-electron-microscope), DSC (differential-scanning-calorimetry), and TGA (thermogravimetric-analyzer) to determine the material properties. From all examinations, adding magnesium and zinc to polyurethane foam affected the compressive strength and porosity of the polyurethane foam. Therefore, all test results concluded that adding magnesium with a composition of 3wt.%, which has a compressive strength of 0.84 MPa, is the best mixture. The idea of finding other compositions that are compatible with the polyurethane will significantly increase the possibility of new materials for aneurysm clip construction.